#TITLE_ALTERNATIVE# - RIDWAN (nim : 10213073), JALA
Econophysics is a field of interdisciplinary research that studies economics with a physics approach. Econophysics is one example of a complex system, in which the parts of it grow into a complex environment collectively. Financial markets are examples of complex systems whose parts relate to each other. Comovement can be interpreted as a positive correlation that explains the phenomenon of the influence of price movements of an asset against the price of other assets. In 2015, the crude oil price decline drastically, this decline of oil price resulted the other stock sectors to be affected. In this research will be analyzed how the Comovement between crude oil prices with five sectors of stock in Indonesia in the period 2014 to 2016. This study used wavelet coherence method and processed using MATLAB. The results obtained in this study there are some stock sectors that have a significant comovement with world oil prices. Differences in the results of each stock sector analysis are then used to determine the best strategy for investors to invest.